MERAJUT KESATUAN DALAM KEBERAGAMAN DI INDONESIA: TINJAUAN TEOLOGIS UNTUK MENGAMALKAN SILA “PERSATUAN INDONESIA” - Mulyo Kadarmanto (Manna Rafflesia, 2018)
This paper aims to discuss and address the phenomenon of unity and unity in Indonesia. Where there have been many events, parties or groups that have tried to undermine the phenomenal unity of the Indonesian people lately. By exploring the theological biblical foundation it is hoped that it can strengthen the foundations of the principle of Indonesian unity, to find a theological basis and be expected to draw implications and relevance for the church to build its participation in realizing Indonesian unity, for the sake of the continuity of Indonesia which is unity in diversity.